WHAT DRIVES THE INTENTION OF MILLENNIALS AND GENERATION Z TO PAY ZIS VIA DIGITAL PLATFORM? RELIGIOSITY AS THE MODERATING VARIABLE - Latipah, Yeni; Supriani , Indri; Sudarsono , Heri (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2024)
Introduction: This study aims to examine the influence of subjective norm attitudes, behavioral control, zakat literacy, trust, and ease-of-use on the intentions of Millennials and Generation Z to give zakat, make donations, and give alms through digital platforms, with religiosity as a moderating factor. Methods: In this study, Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed as the data analysis method. The study involved 202 respondents from Millennials and Generation Z in Indonesia. Results: The study involved 202 respondents from Millennials and Generation Z in Indonesia. The results demonstrate that attitudes, subjective norms, behavioral control, trust, ease of use, and religiosity significantly and positively influence the intention of Millennials and Generation Z to pay ZIS through digital platforms. However, zakat literacy does not impact their intention to use digital platforms for ZIS payments. Additionally, religiosity, when considered as a moderating variable, does not moderate the influence of attitudes, subjective norms, behavioral control, zakat literacy, and trust on the intention of Millennials and Generation Z to pay ZIS digitally. Conclusion and suggestion: This research provides valuable theoretical implications that can be adopted as a reference for future research that employs religiosity as a moderating variable. Most importantly, zakat institutions and the government can use these discoveries to develop policies that highlight the importance of paying ZIS and strengthen societal attitudes towards it, thereby increasing ZIS collection in Indonesia.